Prolonged dual antiplatelet therapy for Chinese ACS patients undergoing emergency PCI with drug-eluting stents: Benefits and risks - Zhang, Yong; Chu, Chao; Zhong, Zhong; Luo, Yong-bai; Ning, Fei-Fei; Guo, Ning (Frontiers in Cardiovascular Medicine, 2023)
Background In patients with acute coronary syndrome (ACS), prolonged dual antiplatelet therapy (DAPT) may reduce ischemic events and increase the risks of bleeding events differently in different ethnic groups. However, whether prolonged DAPT in Chinese patients with ACS following emergency percutaneous coronary intervention (PCI) with drug-eluting stents (DES) will be beneficial or dangerous remains unclear. This study aimed to examine the potential benefits and risks of prolonged DAPT in Chinese patients with ACS who have undergone emergency PCI with DES. Methods This study included 2,249 patients with ACS who underwent emergency PCI. If DAPT was continued for 12 or 12–24 months, it was classified as the standard (n = 1,011) or prolonged (n = 1,238) DAPT group, respectively. The incidence of the following endpoint events was determined and compared between the two groups: composite bleeding event (BARC 1 or 2 types of bleeding and BARC 3 or 5 types of bleeding) and major adverse cardiovascular and cerebrovascular events (MACCEs) [ischemia-driven revascularization, non-fatal ischemia stroke, non-fatal myocardial infarction (MI), cardiac death, and all-cause death]. Results After a median period of 47 months of follow-up [47 (40, 54)], the rate of composite bleeding events was 13.2% (n = 163) in the prolonged DAPT group and 7.9% (n = 80) in the standard DAPT group [odds ratio (OR) 1.765, 95% confidence interval (CI) 1.332–2.338, p < 0.001]. The rate of MACCEs was 11.1% (n = 138) in the prolonged DAPT group and 13.2% (n = 133) in the standard DAPT group (OR 0.828, 95% CI 0.642–1.068, p = 0.146). The DAPT duration was further shown to be insignificantly correlated with MACCEs as per the multivariable Cox regression model (HR, 0.813; 95% CI, 0.638–1.036; p = 0.094). No statistically significant difference was observed between the two groups. However, the DAPT duration was a separate predictor of composite bleeding events according to the multivariable Cox regression model (HR 1.704, 95% CI 1.302–2.232, p < 0.001). Compared with the standard DAPT group, the prolonged DAPT group had substantially more BARC 3 or 5 types of bleeding events (3.0 vs. 0.9% in those with standard DAPT, OR 3.430, 95% CI 1.648–7.141, p < 0.001) and BARC 1 or 2 types of bleeding events (10.2 vs. 7.0% in those with standard DAPT, OR 1.500, 95% CI 1.107–2.032, p = 0.008). Conclusion The prolonged DAPT group had a considerably greater incidence of composite bleeding events than the standard DAPT group. No statistically significant difference was observed in the incidence of MACCEs between the two groups.